An engineered U1 small nuclear RNA rescues splicing‐defective coagulation F7 gene expression in mice. (February 2014) - Balestra, D.; Faella, A.; Margaritis, P.; Cavallari, N.; Pagani, F.; Bernardi, F.; Arruda, V. R.; Pinotti, M.
Summary Background The ability of the spliceosomal small nuclear RNA U1 (U1snRNA) to rescue pre‐mRNA splicing impaired by mutations makes it an attractive therapeutic molecule. Coagulation factor deficiencies due to splicing mutations are relatively frequent and could therefore benefit from this strategy. However, the effects of U1snRNAs in vivo remain unknown. Objectives To assess the rescue of the F7 c.859+5G>A splicing mutation (FVII+5A), causing severe human factor VII (hFVII) deficiency, by the modified U1snRNA+5a (U1+5a) in a murine model. Methods Mice expressing the human F7 c.859+5G>A mutant were generated following liver‐directed expression by plasmid or recombinant adeno‐associated viral (AAV) vector administration. The rescue of the splice‐site defective pre‐mRNA by U1+5a was monitored in liver and plasma through hFVII‐specific assays. Results Injection of plasmids encoding the U1+5a rescued plasma hFVII levels, which increased from undetectable to ~8.5% of those obtained with the wild‐type hFVII plasmid control. To assess long‐term effects, mice were injected with low and high doses of two AAV vectors encoding the FVII+5A splice site mutant as template to be corrected by U1+5a. This strategy resulted in hFVII plasma levels of 3.9 ± 0.8 or 23.3 ± 5.1 ng mL−1 in a dose‐dependent manner, corresponding in patients to circulating FVII levels of ~1–4.5% of normal. Moreover, in both experimental models, we also detected correctly spliced hFVII transcripts and hFVII‐positive cells in liver cells. Conclusions Here we provide the first in vivo proof‐of‐principle of the rescue of the expression of a splicing‐defective F7 mutant by U1snRNAs, thus highlighting their therapeutic potential in coagulation disorders.